Analisis Implementasi Pembiayaan KPR BTN Subsidi pada Nasabah Berpenghasilan Rendah di BTN KCS Padang - Sulistri Mufidah Umah; Ariyun Anisah (ARZUSIN, 2026)
The implementation of KPR BTN Subsidi financing for low-income customers has become an important issue in Islamic banking because it is related to access to home ownership, contract compliance, verification effectiveness, and financing risk management. Although the topic of subsidized mortgages has been examined in several studies, research specifically addressing the implementation of sharia-based financing at BTN Sharia Branch Office (KCS) Padang, particularly regarding financing procedures, the application of sharia contracts, the e-FLPP verification system, financing risk management, and customer education, remains limited. This study aims to analyze the implementation of KPR BTN Subsidi financing for low-income customers at BTN KCS Padang. This study used a qualitative approach with a case study design, involving the management of BTN KCS Padang and customers receiving KPR BTN Subsidi selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of KPR BTN Subsidi financing at BTN KCS Padang was carried out systematically through the stages of financing application, data verification through the e-FLPP system, feasibility surveys, the implementation of murabahah and musyarakah mutanaqisah contracts, and the management of problematic financing risks. The murabahah contract was the most dominantly used contract because it provides certainty regarding the margin and installment amount for low-income customers. The conclusion of this study affirms that the successful implementation of sharia-based subsidized mortgages is strongly determined by contract transparency, the effectiveness of financing verification, risk management, and customer education. These findings contribute to the development of Islamic banking studies and provide practical implications for Islamic financial institutions in strengthening the governance of subsidized home financing that is transparent, accountable, and in accordance with sharia principles.